Argamassa para revestimento com propriedades termoacústicas, produzida a partir de vermiculita expandida e borracha reciclada de pneus - Cintra, Cynthia Leonis Dias (Universidade Federal de São Carlos, 2013)
Light weight masonry mortars containing vermiculite are commonly used when one wants thermal and acoustic insulation. This Thesis investigated the incorporation of recycled used tires rubber crumbs as light weight mortar aggregates, in substitution of parts of vermiculite and sand. The main objective was based on the natural resources protection and decrease in environment impact, by means of the recycling in large quantities, of a problematic dischargeable product (used tires). By means of the pertinent standards, six masonry mortar compositions were investigated; two compositions of light weight masonry mortars containing cement, lime, sand and vermiculite, two compositions containing cement, lime, sand, vermiculite and rubber crumbs from recycled tires. In addition, to have a broader comparative ground ,a traditional mortar (cement+slime+sand) and an industrialized mortar (cemet+lime+sand+additives), not of the light weight class, were also investigated. The substitution of parts of vermiculite and sand by rubber recycled aggregates was taken to 45wt% of the whole light weight mortar mass. The results showed that the incorporation of rubber aggregates, promoted a decrease in the mortar drying shrinkage, a reasonable increase in the compressive strength and an expressive increase in the adherence strength of the light mortars. Another positive factor was that the inclusion of the rubber aggregates did not caused any sensible alteration neither in the thermal conductivity nor on the acoustic absorption, comparatively to the values presented by the light mortars without rubber aggregates. It was concluded that the light weight mortars containing recycled rubber aggregates, constitute a viable new contribution to the sustainable constructive elements field, fulfilling this Thesis main objective.
Masonry mortar with thermo-acustic insulating properies based on vermiculite and recicled rubber aggregates from wasted tires
Keywords: Argamassa; Vermiculita; Borracha reciclada de pneus; Revestimentos; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA